Xylose Improves Antibiotic Activity of Chloramphenicol and Tetracycline against K. pneumoniae and A. baumannii in a Murine Model of Skin Infection - Alejandro A. Hidalgo; Ángel J. Arias; Juan A. Fuentes; Patricia García; Guido C. Mora; Nicolás A. Villagra (Canadian Journal of Infectious Diseases and Medical Microbiology)
Increased resistance to antimicrobials in clinically important bacteria has been widely reported. The major mechanism causing multidrug resistance (MDR) is mediated by efflux pumps, proteins located in the cytoplasmic membrane to exclude antimicrobial drug. Some efflux pumps recognize and expel a variety of unrelated antimicrobial agents, while other efflux pumps can expel only one specific class of antibiotics. Previously, we have reported that xylose decreases the efflux-mediated antimicrobial resistance in Salmonella typhimurium, Pseudomonas aeruginosa, and Acinetobacter baumannii in vitro. In this work, we assessed the effectiveness of combining xylose with antibiotics to kill resistant Acinetobacter baumannii and Klebsiella pneumoniae in a murine model of skin infection. Skin infections were established by seeding 109 bacteria onto eroded skin of mice. Mice treated with the antibiotic alone or with a mixture of glucose and antibiotics or xylose and antibiotics were compared to a control group that was infected but received no further treatment. We observed that the mixtures xylose-tetracycline and xylose-chloramphenicol produced a decrease of at least 10 times viable Acinetobacter baumannii and Klebsiella pneumoniae recovered from infected skin, compared with mice treated with the antibiotic alone. Our results show that xylose improves the antibiotic activity of tetracycline and chloramphenicol against efflux-mediated resistance Acinetobacter baumannii and Klebsiella pneumoniae, in a murine model of skin infection. We envision these combined formulations as an efficient treatment of skin infections with bacteria presenting efflux-mediated resistance, in both humans and animals.